Preparation of enantiomerically pure chelate ligands L2 = XCH2CH(OH)CH2Y from epichlorohydrin - conformation of their L2Rh(COD)+ derivatives and enantioselective hydrogenation by L2Rh(COD)+ - Karas, Jörg; Huttner, Gottfried; Heinze, Katja; Rutsch, Peter; Zsolnai, Laszlo (European journal of inorganic chemistry, 1999)
Enantiomerically pure chelate ligands L2 = XCH2CH(OH)CH2Y (1) are obtained from epichlorohydrin in a two-step synthesis. × and Y may be different types of R2P donor groups, NR2 or SR donors. The OH function of 1 may be transformed into an ether function under specialized conditions. Ligands 1 react with [Rh(COD)Cl]2 in the presence of KPF6 to give the coordination compounds 2, [L2Rh(COD)]+PF6−, as orange, microcrystalline salts. The structures adopted by compounds 2 in the solid state have been analysed by X-ray crystallography in selected cases, and it has been found that the six-membered chelate cycles adopt twist as well as chair conformations depending on the nature of × and Y. In solution, compounds 2 generally show dynamic behaviour, which is in part due to the conformational flexibility of the six-membered cycles. In cases where one of the PR2 donor groups contains ortho-substituted phenyl substituents, rotational isomerism of these groups is an additional dynamic process. For some of these compounds, the nature of the dynamic behaviour has been analysed by variable-temperature NMR experiments. Compounds 2 are found to be precatalysts in the hydrogenation of (Z)-2-acetamidocinnamic acid. The rate of conversion is strongly influenced by the steric bulk of the substituents, with smaller substituents leading to higher rates. Enantiomeric discrimination is high only for those ligands that contain ortho-substituted aryl groups at their PR2 donors. The maximum enantiomeric excess observed was 85% for × = PPh2, Y = P(2-MeOPh)2.